Regioselective synthesis of methyl 5-(N-Boc-cycloaminyl)-1,2-oxazole-4-carboxylates as new amino acid-like building blocks - Bruzgulienė, Jolita; Račkauskienė, Greta; Bieliauskas, Aurimas; Milišiūnaitė, Vaida; Dagilienė, Miglė; Matulevičiūtė, Gita; Martynaitis, Vytas; Krikštolaitytė, Sonata; Sløk, Frank A.; Šačkus, Algirdas (Beilstein Journal of Organic Chemistry, 2022)
A convenient and efficient synthesis of novel achiral and chiral heterocyclic amino acid-like building blocks was developed. Regioisomeric methyl 5-(N-Boc-cycloaminyl)-1,2-oxazole-4-carboxylates were prepared by the reaction of β-enamino ketoesters (including azetidine, pyrrolidine or piperidine enamines) with hydroxylamine hydrochloride. Unambiguous structural assignments were based on chiral HPLC analysis, 1H, 13C, and 15N NMR spectroscopy, HRMS, and single-crystal X-ray diffraction data.
Keywords: β-enamino ketoesters; heterocyclic amino acids; 15N-labeled 1,2-oxazole; NMR (1H; 13C; 15N); 1,2-oxazole (isoxazole); X-ray structure analysis

(untitled) - Sysak, A.; Obmińska-Mrukowicz, B. (Eur. J. Med. Chem., 2017)

(untitled) - Zhu, J.; Mo, J.; Lin, H.-z.; Chen, Y.; Sun, H.-p. (Bioorg. Med. Chem., 2018)

(untitled) - Li, J.; Lin, Z.; Wu, W.; Jiang, H. (Org. Chem. Front., 2020)

(untitled) - Hu, F.; Szostak, M. (Adv. Synth. Catal., 2015)

(untitled) - Zimecki, M.; Bąchor, U.; Mączyński, M. (Molecules, 2018)

(untitled) - Agrawal, N.; Mishra, P. (Med. Chem. Res., 2018)

(untitled) - Morita, T.; Yugandar, S.; Fuse, S.; Nakamura, H. (Tetrahedron Lett., 2018)

(untitled) - Krogsgaard-Larsen, P.; Brehm, L.; Schaumburg, K. (Acta Chem. Scand., Ser. B, 1981)

(untitled) - Obermaier, S.; Müller, M. (Angew. Chem., Int. Ed., 2020)

(untitled) - Madsen, U.; Stensbol, T. B.; Krogsgaard-Larsen, P. (Curr. Med. Chem., 2001)

(untitled) - Krogsgaard-Larsen, P.; Ebert, B.; Lund, T. M.; Bräuner-Osborne, H.; Sløk, F. A.; Johansen, T. N.; Brehm, L.; Madsen, U. (Eur. J. Med. Chem., 1996)

(untitled) - Kim, J.-H.; Marton, J.; Ametamey, S. M.; Cumming, P. (Molecules, 2020)

(untitled) - Sløk, F. A.; Ebert, B.; Lang, Y.; Krogsgaard-Larsen, P.; Lenz, S. M.; Madsen, U. (Eur. J. Med. Chem., 1997)

(untitled) - Bleakman, D.; Lodge, D. (Neuropharmacology, 1998)

(untitled) - Johansen, T. N.; Stensbøl, T. B.; Nielsen, B.; Vogensen, S. B.; Frydenvang, K.; Sløk, F. A.; Brünumuner-Osborne, H.; Madsen, U.; Krogsgaard-Larsen, P. (Chirality, 2001)

(untitled) - Burkhart, D. J.; Twamley, B.; Natale, N. R. (Tetrahedron Lett., 2001)

(untitled) - Cerminara, I.; Chiummiento, L.; Funicello, M.; Guarnaccio, A.; Lupattelli, P. (Pharmaceuticals, 2012)

(untitled) - Bruyat, P.; Jean, L.; Renard, P.-Y. (Eur. J. Org. Chem., 2019)

(untitled) - Sekirnik née Measures, A. R.; Hewings, D. S.; Theodoulou, N. H.; Jursins, L.; Lewendon, K. R.; Jennings, L. E.; Rooney, T. P. C.; Heightman, T. D.; Conway, S. J. (Angew. Chem., Int. Ed., 2016)

(untitled) - Jones, R. C. F.; Hollis, S. J.; Iley, J. N. (Tetrahedron: Asymmetry, 2000)

(untitled) - Chennakrishnareddy, G.; Vasantha, B.; Narendra, N.; Sureshbabu, V. V. (Int. J. Pept. Res. Ther., 2011)

(untitled) - Chalyk, B. A.; Kandaurova, I. Y.; Hrebeniuk, K. V.; Manoilenko, O. V.; Kulik, I. B.; Iminov, R. T.; Kubyshkin, V.; Tverdokhlebov, A. V.; Ablialimov, O. K.; Mykhailiuk, P. K. (RSC Adv., 2016)

(untitled) - Kunig, V.; Potowski, M.; Gohla, A.; Brunschweiger, A. (Biol. Chem., 2018)

(untitled) - Madsen, D.; Azevedo, C.; Micco, I.; Petersen, L. K.; Hansen, N. J. V. (Prog. Med. Chem., 2020)

(untitled) - Blakskjaer, P.; Heitner, T.; Hansen, N. J. V. (Curr. Opin. Chem. Biol., 2015)

(untitled) - Petersen, L. K.; Blakskjær, P.; Chaikuad, A.; Christensen, A. B.; Dietvorst, J.; Holmkvist, J.; Knapp, S.; Kořínek, M.; Larsen, L. K.; Pedersen, A. E.; Röhm, S.; Sløk, F. A.; et al. (Med. Chem. Commun., 2016)

(untitled) - Malinauskienė, V.; Kveselytė, A.; Dzedulionytė, K.; Bieliauskas, A.; Burinskas, S.; Sløk, F. A.; Šačkus, A. (Chem. Heterocycl. Compd., 2018)

(untitled) - Matulevičiūtė, G.; Arbačiauskienė, E.; Kleizienė, N.; Kederienė, V.; Ragaitė, G.; Dagilienė, M.; Bieliauskas, A.; Milišiūnaitė, V.; Sløk, F. A.; Šačkus, A. (Molecules, 2021)

(untitled) - Iškauskienė, M.; Ragaitė, G.; Sløk, F. A.; Šačkus, A. (Mol. Diversity, 2020)

256th National Meeting and Exposition of the American Chemical Society (ACS) - Sackus, A.; Kveselyte, A.; Malinauskiene, V.; Dzedulionyte, K.; Bieliauskas, A.; Burinskas, S.; Krikstolaityte, S.; Sløk, A. F. (Heterocyclic amino acids as scaffolds for the synthesis of functionalized chiral 1,3-thiazole and 1,3-selenazole derivatives, Boston, MA, USA, 19.8.2018-23.8.2018, 2018)

(untitled) - Dzedulionytė, K.; Voznikaitė, P.; Bieliauskas, A.; Malinauskienė, V.; Sløk, F. A.; Šačkus, A. (Molbank, 2021)

(untitled) - Plumet, J. (ChemPlusChem, 2020)

(untitled) - Pinho e Melo, T. M. V. D. (Curr. Org. Chem., 2005)

(untitled) - Silva, R. G. M.; da Silva, M. J. V.; Jacomini, A. P.; Moura, S.; Back, D. F.; Basso, E. A.; Rosa, F. A. (RSC Adv., 2018)

(untitled) - Mittersteiner, M.; Andrade, V. P.; Bonacorso, H. G.; Martins, M. A. P.; Zanatta, N. (Eur. J. Org. Chem., 2020)

WO Pat. Appl. - Gao, W.; Lau, T.; Pan, S.; Phillips, D. P.; Wang, X. (Compounds and compositions as TGR5 agonists, 2012)

(untitled) - Brooks, D. W.; Lu, L. D.-L.; Masamune, S. (Angew. Chem., Int. Ed. Engl., 1979)

(untitled) - Greck, C.; Thomassigny, C.; Le Bouc, G. (ARKIVOC, 2012)

(untitled) - Schofield, M. H.; Sorel, M.-A.; Manalansan, R. J.; Richardson, D. P.; Markgraf, J. H. (Magn. Reson. Chem., 2006)

(untitled) - Deev, S. L.; Khalymbadzha, I. A.; Shestakova, T. S.; Charushin, V. N.; Chupakhin, O. N. (RSC Adv., 2019)

(untitled) - Deev, S. L.; Shenkarev, Z. O.; Shestakova, T. S.; Chupakhin, O. N.; Rusinov, V. L.; Arseniev, A. S. (J. Org. Chem., 2010)

(untitled) - Chen, B. C.; Von Philipsborn, W.; Nagarajan, K. (Helv. Chim. Acta, 1983)

(untitled) - Maslova, M. M.; Pol'shakov, V. I.; Anisimova, O. S.; Marchenko, N. B.; Glushkov, R. G. (Pharm. Chem. J., 1993)

(untitled) - Akiba, K.; Kashiwagi, K.; Ohyama, Y.; Yamamoto, Y.; Ohkata, K. (J. Am. Chem. Soc., 1985)

(untitled) - Avenoza, A.; Busto, J. H.; Corzana, F.; Jiménez-Osés, G.; Peregrina, J. M. (Tetrahedron, 2003)

(untitled) - Garner, P.; Park, J. M. (J. Org. Chem., 1987)

(untitled) - Hu, D. X.; Grice, P.; Ley, S. V. (J. Org. Chem., 2012)

(untitled) - Allen, F. H.; Kennard, O.; Watson, D. G.; Brammer, L.; Orpen, A. G.; Taylor, R. (J. Chem. Soc., Perkin Trans. 2, 1987)